Healthcare Expenditures Channel of Natural Resource Curse: The Case of Gulf Cooperation Council Countries - Erdoğan, Seyfettin; Çevik, Emrah İsmail; Gedikli, Ayfer (International Journal of Energy Economics and Policy, 2020)
The fact that the increase in natural resource revenues is not adequately transferred to human capital investments is one of the main reasons for explaining the weak economic growth performance. The findings of numerous studies investigating the relationship between healthcare expenditures and natural resource abundance in natural resource-rich countries confirm this assertion. These findings can be considered as a source of information in the process of determining the policies regarding human capital investments to be implemented in natural resource-rich countries. The aim of this study is to investigate the relationship between the abundance of natural resources and health expenditures by using data from 2000 to 2016 for GCC (Gulf Cooperation Council) member countries consisting of United Arab Emirates, Bahrain, Qatar, Kuwait, Saudi Arabia and Oman. The empirical results indicated that there is no causal relationship between the variables of GCC countries except Bahrain and UAE. This result shows that the resource curse hypothesis is partially valid. Therefore, GCC countries aiming to increase their economic growth performances by implementing a diversification strategy in production should allocate more sources to health expenditures in order to increase their labor efficiency. Keywords: healthcare expenditures, natural resource, Gulf Cooperation Council member countries JEL Classifications: H51, N55, J24 DOI: https://doi.org/10.32479/ijeep.8667